Uncovering Lymphatic Transport Abnormalities in Patients with Primary Lipedema - Gould, Daniel J.; El-Sabawi, Bassim; Goel, Pedram; Badash, Ido; Colletti, Patrick; Patel, Ketan M. (Journal of Reconstructive Microsurgery, 2020)
Background Although lipedema is often clinically distinguished from lymphedema, there is considerable overlap between the two entities. The purpose of this study was to evaluate lymphoscintigraphic findings in patients with lipedema to better characterize lymphatic flow in this patient population.Methods Patients with lipedema receiving lymphoscintigraphy between January 2015 and October 2017 were included. Patient demographics, clinical characteristics, and lymphoscintigraphic findings were extracted. Klienhan's transport index (TI) was utilized to assess lymphatic flow in patient's lower extremities (LEs).Scores ranged from 0 to 45, with values > 10 denoting pathologic lymphatic transport.Results A total of 19 total patients with lipedema underwent lymphoscintigraphic evaluation. Mean age was 54.8 years and mean body mass index was 35.9 kg/m2. Severity of lipedema was classified as stage 1 in five patients (26.3%), stage 2 in four patients (21.1%), stage 3 in four patients (21.1%), and stage 4 in six patients (31.6%). The mean TI for all extremities was 12.5; 24 (63.2%) LEs had a pathologic TI, including 7 LEs with stage 1 (29.2%), 3 LEs with stage 2 (12.5%), 6 LEs with stage 3 (25.0%), and 8 LEs with stage 4 lipedema (33.3%). The mean TI was significantly greater for extremities with severe (stage 3/4) lipedema than those with mild or moderate (stage 1/2) lipedema (15.1 vs. 9.7, p = 0.049). Mean difference in TI scores between each LE for individual patients was 6.43 (standard deviation +7.96).Conclusion Our results suggest that patients with lipedema have impaired lymphatic transport, and more severe lipedema may be associated with greater lymphatic transport abnormalities.
Keywords: lipedema; lymphedema; lymphatic transport abnormalities